Let's go! [compact disc] - Berkner, Laurie (Two Tomatoes Records, 2021)
Laurie Berkner's fourteenth album showers her ever-growing list of fans with an inspiring array of original, interactive sons in her signature style, famous for its clarity, warmth, and wisdom. The album reflects the evolving experiences of day-to-day life for kids and their adults. It helps kids step into the future without forgetting to love who they are in the here-and-now.